Preparation method and application of metal nanoparticle embedded zinc oxide nanorod array

Zinc oxide nanorods are grown through magnetron sputtering technology and embedded in nano-scale metal particles, and an efficient solar energy absorption coating is prepared, which solves the problems of complex processes and insufficient metal nanoparticles in the existing technology, and achieves efficient solar spectrum absorption and good thermal stability.

CN115889759BActive Publication Date: 2025-04-11WUHAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211484097.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-04-11
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The prior art When preparing solar energy absorbing coatings, the process is complex, the equipment requirements are high, difficult to control and suitable for mass production, and the metal nanoparticles are not strong enough and difficult to apply directly.

Method used

Through magnetron sputtering technology, the running speed and trajectory of atoms and ion flow are controlled, zinc oxide nanorods are grown and nano-scale metal particles are embedded to prepare textured selective solar energy absorption coatings.

Benefits of technology

It achieves efficient solar spectrum absorption, improves the absorption efficiency of solar energy absorption coating, and has good thermal stability and appropriate cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115889759B_ABST
    Figure CN115889759B_ABST
Patent Text Reader

Abstract

The present application discloses a preparation method and application of zinc oxide nanorod arrays inlaid with metal nanoparticles. In this scheme, zinc oxide nanorods and inlaid nanoscale metal particles are grown by controlling the running speed and trajectory of atoms and ion flows to prepare a textured selective solar absorption coating. The method is based on magnetron sputtering and changes the position of the substrate. The substrate is placed back to the direction of the atoms and ion flows, so that the speed of the atoms and ion flows is reduced when they move near the substrate surface, and the movement is non-directional. This atomic and ion flow speed control method effectively prepares zinc oxide nanorods on the surface of stainless steel and pure metal substrates such as Cu, Al, and Cr to form a textured surface, and inlaid with nanoscale metal particles such as Ag, Cu, Au, and Cr. The textured surface of the zinc oxide nanorods and the metal nanoparticles work together to increase the absorption of sunlight through the local surface plasma resonance effect, and is successfully applied to solar spectrum absorption coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coating preparation, and in particular to a preparation method and application of a metal nanoparticle-embedded zinc oxide nanorod array. Background Art

[0002] With the consumption of fossil energy, the problem of energy shortage has become increasingly prominent. At the same time, the development and use of traditional fossil energy has brought about a series of environmental problems. As a clean energy, solar energy has the characteristics of large total amount and wide distribution. Its development and utilization is an important way to achieve the sustainable development strategy of human society. Concentrated solar thermal conversion system (CSP) is considered to be the most environmentally friendly and efficient solar energy utilization technology. The coating deposited on the receiver converts solar energy into thermal energy.

[0003] The textured surface is composed of micro-nanoscale structures. Due to its undulating morphology, it can effectively capture the solar spectrum. The purpose is to make the incident sunlight reflect multiple times on the textured surface, reduce the reflectivity, and achieve a spectral absorption effect. Therefore, it can effectively absorb short waves equivalent to the texture size, while being transparent to long-wave radiation. Currently, textured surfaces have been prepared on materials such as W, Cu, Cr, stainless steel, copper oxide, and alloys, which effectively improve the solar spectrum absorption rate. At the same time, because its textured surface has a higher surface area, the element diffusion area is increased, and the diffusion process is greatly prolonged, making it have better thermal stability than metal ceramics and multilayer coatings.

[0004] Another way to achieve absorption of solar radiation is to use metal nanoparticles. If the metal particles are small enough (5-100nm), they become very efficient in absorbing visible light due to the localized surface plasmon resonance effect. For solar absorption coatings, it is not convenient to use metal nanoparticles directly, as such materials are not strong enough. Therefore, in traditional solar absorption coatings, metal nanoparticles are often embedded in a transparent dielectric matrix, which is called a metal ceramic absorption coating.

[0005] At present, researchers generally use processes such as metal oxidation, hydrothermal method, and ion beam etching to construct self-assembled 2D nanostructures, foam nanostructures and other textured surfaces on the surfaces of transition metals, Fe-Cr-Ni alloys, metal ceramics, etc. However, the former two have high requirements on the precision of chemical conditions, are difficult to control, and are not suitable for mass production. Ion beam etching has high requirements on equipment and requires the participation of skilled engineers, and its operability is relatively weak. Summary of the invention

[0006] In view of this, the present application provides a preparation method and application of a metal nanoparticle-embedded zinc oxide nanorod array, which has good solar spectrum absorption efficiency when applied to a solar spectrum absorption coating.

[0007] The creation process of the invention is as follows: The preparation method involved in the technical solution is to grow zinc oxide nanorods and embed nano-scale metal particles by controlling the running speed and trajectory of atoms and ions, so as to prepare a textured selective solar absorption coating. The method is based on magnetron sputtering, and the substrate position is innovatively and cleverly changed. The substrate is placed back to the direction of the atoms and ions, so that the speed of the atoms and ions is reduced when they move near the substrate surface, and the movement is non-directional. This atomic and ion flow speed control method effectively prepares zinc oxide nanorods on the surface of stainless steel and pure metal substrates such as Cu, Al, and Cr, forming a textured surface. On this basis, nano-scale metal particles such as Ag, Cu, Au, and Cr are embedded. The textured surface of the zinc oxide nanorods and the metal nanoparticles work together to increase the absorption of sunlight through the local surface plasma resonance effect, and are successfully applied to solar spectrum absorption coatings.

[0008] In a first aspect, the present application provides a method for preparing a metal nanoparticle-embedded zinc oxide nanorod array, comprising the following steps:

[0009] (A) placing the substrate in a magnetron sputtering chamber with its surface to be deposited facing the direction of the atomic ion flow, and performing magnetron sputtering on the surface to be deposited in this forward placement to etch and form a rough adhesion surface;

[0010] (B) placing the substrate in a magnetron sputtering chamber with its rough surface facing away from the direction of atomic ion flow, and performing magnetron sputtering on the rough surface to deposit ZnO nanorods based on the reverse placement posture;

[0011] (C) Based on the reverse placement posture, magnetron sputtering is performed on the rough adhesion surface deposited with ZnO nanorods to form nanoparticle-embedded zinc oxide nanorod arrays.

[0012] Suitably but not restrictively, in step (A), the substrate and the sputtering target are parallel and the distance between them is 3-10 cm.

[0013] Suitable but not restrictive, in step (A), the conditions for magnetron sputtering are: the temperature in the magnetron sputtering chamber is heated to 100-300°C, 0.5-5Pa Ar gas is introduced, the arc power supply is turned on, and the current of the arc power supply is 50-150A to form Ar + Ion beam, Ar at -50~-300V bias + The plasma beam bombards the substrate for 10 minutes to 90 minutes.

[0014] The purpose of the rough adhesion surface is to increase the adhesion of subsequent coatings and to enhance the absorption of the solar spectrum by roughening the surface.

[0015] Suitably, but not limitingly, the rough adhesion surface has a root mean square roughness of 10-120 nm.

[0016] Suitable but not limiting, in step (B), the substrate and the sputtering target are parallel and the distance between them is 3-10 cm.

[0017] Suitably but not limitingly, in step (B):

[0018] The conditions for magnetron sputtering are as follows: the vacuum degree in the magnetron sputtering chamber is reduced to 2×10 -3 ~8×10 -3 Pa, and at the same time, the temperature in the cavity is heated to 100-300℃, and 1-5Pa Ar and O2 mixed gas is introduced, the Ar / O2 volume ratio is 1 / 3-3 / 1, and the power of the RF power supply is 300-1000W.

[0019] The specific process of magnetron sputtering to form deposited ZnO nanorods is as follows: the target material is sputtered by Ar + The ions are bombarded and sputtered to form a directional ion flow, which hits the back of the substrate to form a dense ZnO film. The ion flow hits the back of the substrate and the substances in the ion flow collide with each other, turning into non-directional motion with the same probability in all directions. During the collision, the target material loses energy and the ion flow speed decreases. At the same time, under the action of the concentration gradient, the high-concentration target material near the back of the substrate will diffuse and move to the vicinity of the substrate surface, that is, the target material diffuses from the directional ion motion area to the diffused ion non-directional motion area, thereby depositing on the roughened substrate surface to form ZnO nanorods.

[0020] Suitably but not limitingly, the magnetron sputtering deposition time is 0.5-10 hours.

[0021] Optionally, in step (C):

[0022] The conditions for magnetron sputtering are as follows: the vacuum degree in the magnetron sputtering chamber is reduced to 2×10 -3 ~8×10 -3 Pa, the temperature in the magnetron sputtering chamber is heated to 100-300°C, 1-5Pa high-purity Ar gas is introduced, and the RF power is 300-1000W;

[0023] The specific process of magnetron sputtering to obtain nanoparticle-embedded zinc oxide nanorod arrays is as follows: metal elements are sputtered under the action of radio frequency and Ar gas flow, and metal particles are deposited on the sides and surface of ZnO nanorods by the same principle. Since the concentration of metal atoms and ions on the substrate surface is low, when the nanoparticles cover the ZnO nanorods, the metal coating grows slowly, and nanoscale metal particles are easily obtained.

[0024] Suitably but not limitingly, the deposition time is 0.5 hours to 5 hours.

[0025] Optionally, the substrate includes a Cu, Al, Cr pure metal substrate and a stainless steel substrate.

[0026] Optionally, in step (A), the substrate is further cleaned before being placed, and the cleaning includes cleaning the front and back sides of the substrate, and deionized water, acetone, and ethanol are used in sequence for step-by-step cleaning, and the step-by-step cleaning time is 3-10 minutes to remove visible pollutants, stubborn pollutants such as oil stains, and acetone residual liquid in sequence. After cleaning, the substrate is placed in a dust-free container, and the ethanol is naturally evaporated before being placed in a magnetron sputtering chamber.

[0027] Optionally, in step (B), the sputtering target is a Zn or ZnO target material providing a nanorod raw material;

[0028] Preferably, in step (C), the sputtering target is a target material of Ag, Cu, Au or Cr that provides a raw material for nano-scale metal particles.

[0029] It is worth adding that the nanorods prepared according to the present application have a length of 5 micrometers to 15 micrometers and a diameter of 0.2 micrometers to 1 micrometer.

[0030] The diameter of the nano-scale metal particles prepared according to the present application is 20 nanometers to 200 nanometers.

[0031] It is easy to understand that the nanorods prepared in the present application include but are not limited to Ag@ZnO, Cr@ZnO, etc., and are not limited thereto, and are determined according to the nanoscale metal particle raw materials, the spectral absorption coating performance requirements and the type of environment used.

[0032] In a second aspect, the present application provides an application of the metal nanoparticle-embedded zinc oxide nanorod array obtained by the above-mentioned preparation method, which is applied to a solar spectrum absorbing coating.

[0033] Compared with the prior art, this application has the following beneficial effects:

[0034] (1) Compared with traditional solar energy absorption coatings, the coating prepared in the present application has novel morphology and structure. It is a combination of the textured surface of zinc oxide nanorods and nanoscale metal particles. The two work together to increase the absorption of sunlight through the local surface plasmon resonance effect and are successfully applied to solar spectrum absorption coatings.

[0035] (2) The zinc oxide nanorods prepared in the present application provide the originally flat substrate with a textured surface. The undulating morphology thereof promotes the effective capture of the solar spectrum, so that the incident sunlight is reflected multiple times on the textured surface, greatly reducing the reflectivity and achieving a spectral absorption effect.

[0036] (3) The nanoscale metal particles embedded on the surface of the nanorods prepared in the present application can further increase the absorption of sunlight through the local surface plasmon resonance effect.

[0037] (4) The ZnO nanorods prepared by this method are uniform in size, with a length of 5 microns to 15 microns and a diameter of 0.2 microns to 1 micron. Nanoscale metal particles are embedded on the surface of the nanorods and are evenly distributed, with a diameter of 20 nanometers to 200 nanometers.

[0038] (5) The size of ZnO nanorods and nanoscale metal particles prepared by the present technology is controllable and adjustable. The specific morphology and density can be achieved by adjusting the distance between the substrate and the target, the temperature in the chamber, the gas atmosphere and pressure, the deposition time, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The technical solution and other beneficial effects of the present application will be made apparent by describing in detail the specific implementation methods of the present application in conjunction with the accompanying drawings.

[0040] Figure 1 (a) is a schematic diagram of preparing a rough surface. Figure 1 (b) Schematic diagram of the deposition of ZnO nanorods and nanoscale metal particles.

[0041] Figure 2 (a) is a roughened surface prepared on the front side of the substrate. Figure 2 (b) is the ZnO nanorods grown on the roughened surface. Figure 2 (c) Nanoscale metal particles embedded on ZnO nanorods.

[0042] Figure 3 (a) is a low-magnification SEM image; Figure 3 (b) is a high-magnification SEM image.

[0043] Figure 4 The figure shows the reflectance spectra of three samples, namely, the reflectance spectrum of the spectral absorption coating comprising zinc oxide nanorods and nanoscale Ag metal particles embedded thereon prepared in the present application, the reflectance spectrum of the spectral absorption coating comprising only zinc oxide nanorods prepared by a traditional hydrothermal method, and the reflectance spectrum of a pure Cu substrate without zinc oxide nanorods and nanoscale Ag metal particles. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0045] Example 1

[0046] This embodiment provides a method for growing zinc oxide nanorods and inlaid nanoscale metal particles by controlling the speed and trajectory of atoms and ion flows to prepare a textured selective solar absorption coating. The surface morphology of the prepared zinc oxide nanorods and metal particles is adjustable, and the specific morphology is controlled by regulating parameters such as the distance between the substrate and the target material, the temperature in the cavity, the gas atmosphere and pressure, and the deposition time.

[0047] Figure 1 , Figure 2 The operation process of coating preparation and sample morphology changes are shown, including the following steps:

[0048] Step 1: Place the substrate in the forward direction, such as Figure 1 (a): Prepare the required substrate, after cleaning and cutting, place it in the magnetron sputtering vacuum chamber, and place it in the forward direction, that is, facing the direction of the atomic and ion flow, and the substrate is parallel to the sputtering target with a spacing of 3-10 cm;

[0049] Step 2: Prepare the rough surface: Use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 2×10 -3 ~8×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 100-300°C, 0.5-5Pa high-purity Ar gas is introduced, and the arc power supply is turned on (current is 50-150A) to form Ar + Ion beam 4, Ar at -50 to -300 V bias + The plasma beam bombards the substrate for 10 to 90 minutes, and etches a rough surface with a root mean square roughness of 10 to 120 nm on the substrate surface. Figure 2 (a) to increase the adhesion of subsequent coatings and enhance the absorption of the solar spectrum by roughening the surface;

[0050] Step 3: Place the substrate in reverse, such as Figure 1 (b): Rotate the substrate to change the direction of the roughened substrate and place it in reverse, that is, facing away from the direction of the atomic and ion flow. The substrate is still parallel to the sputtering target with a spacing of 3-10 cm.

[0051] Step 4: Deposition of ZnO nanorods: Select a suitable sputtering target and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 2×10 -3 ~8×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 100-300℃, and 1-5Pa high-purity Ar and O2 mixed gas is introduced, with the Ar / O2 volume ratio of 1 / 3 to 3 / 1. The RF power supply (power is 300-1000W) is turned on. Under the action of RF and Ar gas flow, the target material is Ar +The target material is sputtered by ion bombardment to form a directional ion flow, which hits the back of the substrate to form a dense ZnO film. The ion flow hits the back of the substrate and the substances in the ion flow collide with each other, turning into non-directional motion with the same probability in all directions. During the collision, the target material loses energy and the ion flow speed decreases. At the same time, under the action of the concentration gradient, the high-concentration target material near the back of the substrate will diffuse and move to the vicinity of the substrate surface, that is, the target material diffuses from the directional ion motion area to the non-directional motion area of ​​the diffused ions, thereby depositing on the roughened substrate surface to form ZnO nanorods, such as Figure 2 (b), deposition time is 0.5 hours to 10 hours;

[0052] Step 5: Deposition of nano-scale metal particles: Keep the substrate in reverse position, select a suitable metal sputtering target, and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 2×10 -3 ~8×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 100-300℃, 1-5Pa high-purity Ar gas is introduced, and the RF power supply (power is 300-1000W) is turned on. Under the action of RF and Ar gas flow, metal elements are sputtered out. The same principle is used to deposit metal particles on the side and surface of ZnO nanorods, such as Figure 2 (c) Due to the low concentration of metal atoms and ions on the substrate surface, when the nanoparticles cover the ZnO nanorods, the metal coating grows slowly and nanoscale metal particles are easily obtained. The deposition time is 0.5 hours to 5 hours.

[0053] Furthermore, in step 1, the substrate includes pure metal substrates such as Cu, Al, Cr, and stainless steel substrates.

[0054] Furthermore, in step 1, the cleaning includes cleaning the front and back sides of the substrate, and a three-step cleaning method of deionized water-acetone-ethanol is adopted, and each step takes 3-10 minutes to remove visible pollutants such as dust, stubborn pollutants such as oil, and acetone residual liquid in turn. After cleaning, it needs to be placed in a dust-free container, and after the ethanol evaporates naturally, it can be placed in the magnetron sputtering chamber.

[0055] Furthermore, in step 4, the sputtering target is a Zn or ZnO target material that provides nanorod raw materials.

[0056] Furthermore, in step 4, the sputtering target is Ag, Cu, Au, or Cr target material that provides nano-scale metal particle raw materials.

[0057] Furthermore, the nanorods prepared according to the present application have a length of 5 micrometers to 15 micrometers and a diameter of 0.2 micrometers to 1 micrometer.

[0058] Furthermore, the diameter of the nano-scale metal particles prepared according to the present application is 20 nanometers to 200 nanometers.

[0059] Example 2

[0060] Combination Figure 3 (a)-(b) are illustrated by taking the preparation of a spectral absorption coating of zinc oxide nanorods and nanoscale Ag metal particles embedded thereon as an example.

[0061] Step 1: Place the substrate in the forward direction, such as Figure 1 (a): Prepare the required stainless steel substrate, after cleaning and cutting, place it in the magnetron sputtering vacuum chamber, and place it in the forward direction, that is, facing the direction of the atomic and ion flow, and the substrate is parallel to the sputtering target with a distance of 7 cm;

[0062] Step 2: Prepare the rough surface: Use a vacuum pump to reduce the vacuum level in the magnetron sputtering chamber to 8×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 200°C, 1Pa of high-purity Ar gas is introduced, and the arc power supply (current is 100A) is turned on to form Ar + Ion beam, Ar at -200V bias + The plasma beam bombards the substrate for 60 minutes, etching the substrate surface to form a rough surface with a root mean square roughness of about 20 nm to increase the adhesion of subsequent coatings and enhance the absorption of the solar spectrum by roughening the surface;

[0063] Step 3: Place the substrate in reverse: Rotate the substrate to change the direction of the roughened substrate and place it in reverse, that is, facing away from the direction of the atomic and ion flow. The substrate is still parallel to the sputtering target with a spacing of 7 cm.

[0064] Step 4: Deposition of ZnO nanorods: Select the pressed ZnO as the sputtering target, and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 5×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 150°C, and 2Pa of high-purity Ar and O2 mixed gas is introduced, with the Ar / O2 volume ratio of 2 / 1. The RF power supply (power is 700W) is turned on. Under the action of RF and Ar gas flow, the target material is Ar + The ions are bombarded and sputtered to form a directional ion flow, which hits the back of the substrate to form a dense ZnO film. The ion flow hits the back of the substrate and the substances in the ion flow collide with each other, turning into non-directional motion with the same probability in all directions. During the collision, the target material loses energy and the ion flow speed is weakened. At the same time, under the action of the concentration gradient, the high-concentration target material near the back of the substrate will diffuse and move to the vicinity of the substrate surface, that is, the target material diffuses from the directional ion motion area to the diffused ion non-directional motion area, thereby depositing on the roughened substrate surface to form ZnO nanorods. The deposition time is 4 hours.

[0065] Step 5: Deposition of nano-scale Ag metal particles: Keep the substrate in reverse position, select Ag metal sputtering target, and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 5×10 -3 Pa, and at the same time, the temperature in the cavity is heated to 100°C, 1Pa high-purity Ar gas is introduced, and the RF power supply (power is 700W) is turned on. Under the action of RF and Ar gas flow, metal elements are sputtered. The same principle is used to deposit metal particles on the side and surface of ZnO nanorods. Due to the low concentration of metal atoms and ions on the surface of the substrate, when the nanoparticles cover the ZnO nanorods, the Ag metal coating grows slowly, and nanoscale metal particles are easy to obtain. The deposition time is 1.5 hours.

[0066] The surface morphology was measured by scanning electron microscopy (SEM), and the surface element composition was measured by energy dispersive spectrometer (EDS). Figure 3 As shown, Figure 3 (a) is a low-magnification SEM image; Figure 3 (b) is a high-magnification SEM image. Figure 3 It can be clearly seen in (a) that the cylindrical ZnO nanorods are of uniform size, about 7 μm in length and 0.5 μm in diameter. Figure 3 In (b), it can be clearly observed that the spherical nanoscale Ag metal particles embedded in the ZnO nanorods have a uniform particle size of about 100 nanometers. It can be seen that the technology for controlling the speed and trajectory of atoms and ion flows provided by the present application can effectively prepare zinc oxide nanorods and embed nanoscale metal particles on their surface, and the zinc oxide nanorods and nanoscale metal particles have the same size and are evenly distributed.

[0067] Example 3

[0068] Combination Figure 4 , taking the measurement of reflectance spectra of three samples (a spectral absorption coating comprising zinc oxide nanorods and nanoscale Ag metal particles embedded thereon prepared by the technology of the present application, a spectral absorption coating comprising only zinc oxide nanorods prepared by a traditional hydrothermal method, and a pure Cu substrate without zinc oxide nanorods and nanoscale Ag metal particles) as an example for explanation.

[0069] Step 1: Place the substrate in the forward direction, such as Figure 1 (a): Prepare the required pure Cu substrate, after cleaning and cutting, place it in the magnetron sputtering vacuum chamber, and place it in the forward direction, that is, facing the direction of the atomic and ion flow, and the substrate is parallel to the sputtering target with a distance of 7 cm;

[0070] Step 2: Prepare the rough surface: Use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 6×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 200 °C, 0.8 Pa of high-purity Ar gas is introduced, and the arc power supply (current is 120 A) is turned on to form Ar+ Ion beam, Ar at -150V bias + The plasma beam bombards the substrate for 30 minutes, etching the substrate surface to form a rough surface with a root mean square roughness of about 100 nm to increase the adhesion of subsequent coatings and enhance the absorption of the solar spectrum by roughening the surface;

[0071] Step 3: Place the substrate in reverse: Rotate the substrate to change the direction of the roughened substrate and place it in reverse, that is, facing away from the direction of the atomic and ion flow. The substrate is still parallel to the sputtering target with a spacing of 7 cm.

[0072] Step 4: Deposition of ZnO nanorods: Select the pressed ZnO as the sputtering target, and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 5×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 150 ° C, and 2.5 Pa of high-purity Ar and O2 mixed gas is introduced, with an Ar / O2 volume ratio of 2 / 1. The RF power supply (power is 700 W) is turned on. Under the action of RF and Ar gas flow, the target material is Ar + The target material is sputtered by ion bombardment to form a directional ion flow, which hits the back of the substrate to form a dense ZnO film. The ion flow hits the back of the substrate and the substances in the ion flow collide with each other, which is transformed into a non-directional motion with the same probability in all directions. During the collision, the target material loses energy and the ion flow speed is weakened. At the same time, under the action of the concentration gradient, the high-concentration target material near the back of the substrate will diffuse and move to the vicinity of the substrate surface, that is, the target material diffuses from the directional ion motion area to the diffused ion non-directional motion area, thereby depositing on the roughened substrate surface to form ZnO nanorods. The deposition time is 8 hours.

[0073] Step 5: Deposition of nano-scale Ag metal particles: Keep the substrate in reverse position, select Ag metal sputtering target, and use a vacuum pump to reduce the vacuum degree in the magnetron sputtering chamber to 5×10 -3 Pa, and at the same time, the temperature in the chamber is heated to 150°C, 1Pa high-purity Ar gas is introduced, and the RF power supply (power is 700W) is turned on. Under the action of RF and Ar gas flow, metal elements are sputtered. The same principle is used to deposit metal particles on the side and surface of ZnO nanorods. Due to the low concentration of metal atoms and ions on the surface of the substrate, when nanoparticles cover the ZnO nanorods, the Ag metal coating grows slowly, and nanoscale metal particles are easily obtained. The deposition time is 0.5 hours;

[0074] Step 6: Measure the reflection spectrum in the full spectrum band and the 0.25-2.5μm coating reflectivity R by using a spectrophotometer and a Fourier spectrometer, and then calculate the absorptivity α in the solar spectrum band, the self-thermal radiation rate ε in the infrared band, and the spectral absorption selectivity α / ε respectively;

[0075] The conversion formula of coating absorptivity and reflectivity in the solar spectrum band (0.3-2.5μm):

[0076]

[0077] The conversion formula of the coating's own thermal emissivity and reflectivity in the infrared band (2.5-25μm):

[0078]

[0079] In the above formula, R, α, and ε are reflectivity, absorptivity, and thermal emissivity, respectively. It can be seen that the higher the reflectivity R, the lower the coating absorptivity α and thermal emissivity ε. λ is the wavelength of solar or thermal radiation, I sol (λ) is the solar radiation under AM1.5, R(λ) is the spectral reflectance, I b (λ) is the spectral thermal emissivity of an absolute black body at room temperature.

[0080] The reflectance spectra of three samples (the spectral absorption coating comprising zinc oxide nanorods and nano-sized Ag metal particles embedded thereon prepared by the present application, the spectral absorption coating comprising only zinc oxide nanorods prepared by the traditional hydrothermal method, and the pure Cu substrate without zinc oxide nanorods and nano-sized Ag metal particles) are shown in FIG. Figure 4 As shown;

[0081] like Figure 4 , respectively show the reflection spectrum of the spectral absorption coating comprising zinc oxide nanorods and nanoscale Ag metal particles embedded thereon prepared by the present application, the reflection spectrum of the spectral absorption coating comprising only zinc oxide nanorods prepared by the traditional hydrothermal method, and the reflection spectrum of a pure Cu substrate without zinc oxide nanorods and nanoscale Ag metal particles.

[0082] from Figure 4 We can clearly see that the reflectance spectral curves corresponding to the three samples are completely different. In the solar spectrum band (0.3-2.5μm), compared with the hydrothermal curve and the curve of the pure substrate, the reflectivity of the solar spectrum water-absorbing coating of Ag@ZnO prepared by the present application is closest to 0, which means it has the best spectral absorption performance. After calculation, the spectral absorption coating prepared by the present application, which includes zinc oxide nanorods and nano-scale Ag metal particles embedded thereon, has the maximum absorptivity (0.97) and spectral absorption selectivity (13.9), which is much better than the spectral absorption coating with only zinc oxide nanorods prepared by the traditional hydrothermal method and the pure Cu substrate without zinc oxide nanorods and nano-scale Ag metal particles.

[0083] It can be seen that the zinc oxide nanorods prepared in the present application give the originally flat substrate a textured surface, and its undulating morphology promotes the effective capture of the solar spectrum, so that the incident sunlight is reflected multiple times on the textured surface, greatly reducing the reflectivity and achieving a spectral absorption effect; the nanoscale metal particles embedded in the surface of the nanorods further prepared in the present application can further increase the absorption of sunlight through the local surface plasmon resonance effect.

[0084] The following table shows the absorptivity α, thermal emissivity ε and spectral absorption selectivity α / ε of each coating in Example 3.

[0085]

[0086] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be covered within the protection scope of the present application.

Claims

1. A method for preparing a metal nanoparticle-embedded zinc oxide nanorod array, characterized in that: The following steps are involved: (A) placing the substrate in a magnetron sputtering chamber with its surface to be deposited facing the direction of the atomic ion flow, and performing magnetron sputtering on the surface to be deposited in this forward placement to etch and form a rough adhesion surface; The conditions for magnetron sputtering are as follows: the temperature in the magnetron sputtering chamber is heated to 100-300°C, 0.5-5Pa Ar gas is introduced, the arc power supply is turned on, and the current of the arc power supply is 50-150A to form Ar + Ion beam, Ar at -50~-300V bias + The plasma beam bombards the substrate for 10 to 90 minutes; the root mean square roughness of the rough adhesion surface is 10-120nm; (B) placing the substrate in a magnetron sputtering chamber with its rough surface facing away from the atomic ion flow direction, and performing magnetron sputtering on the rough surface based on the reverse placement posture to form deposited ZnO nanorods; The conditions for magnetron sputtering are as follows: the vacuum degree in the magnetron sputtering chamber is reduced to 2×10 -3 ~8×10 -3 Pa, while heating the chamber temperature to 100-300°C, introducing 1-5Pa Ar and O2 mixed gas, the Ar / O2 volume ratio is 1 / 3- 3 / 1, the power of the RF power supply is 300-1000W; the magnetron sputtering deposition time is 0.5-10 hours; The sputtering target is one of Zn and ZnO targets providing nanorod raw materials; (C) Based on the reverse placement posture, magnetron sputtering is performed on the rough attachment surface deposited with ZnO nanorods to form nanoparticle-embedded ZnO nanorod arrays; The conditions for magnetron sputtering are as follows: the vacuum degree in the magnetron sputtering chamber is reduced to 2×10 -3 ~8×10 -3 Pa, the temperature in the magnetron sputtering chamber is heated to 100-300°C, 1-5Pa high-purity Ar gas is introduced, the RF power is 300-1000W; the deposition time is 0.5 hours-5 hours; The sputtering target is one of Ag, Cu, Au, and Cr targets that provide nano-scale metal particle raw materials.

2. The preparation method according to claim 1, characterized in that: In step (A), the substrate and the sputtering target are parallel and the distance between them is 3-10 cm.

3. The preparation method according to claim 1, characterized in that: In step (B), the substrate and the sputtering target are parallel and the distance between them is 3-10 cm.

4. The preparation method according to claim 1, characterized in that: The substrate is one of a Cu, Al, Cr pure metal substrate and a stainless steel substrate.

5. The preparation method according to claim 1, characterized in that: In the step (A), the substrate is cleaned before being placed, and the cleaning includes cleaning the front and back sides of the substrate, and a step-by-step cleaning method is implemented in sequence using deionized water, acetone, and ethanol. The step-by-step cleaning time is 3-10 minutes. After cleaning, the substrate is placed in a dust-free container, and the ethanol is naturally volatilized before being placed in a magnetron sputtering chamber.

6. An application of a metal nanoparticle-embedded zinc oxide nanorod array obtained by the preparation method according to any one of claims 1 to 5, characterized in that: Applied to solar spectrum absorbing coatings.

Citation Information

Patent Citations

  • Method for preparing zinc and zinc oxide nano material with controllable appearance by utilizing magnetron sputtering

    CN101570853A

  • Ag-ZnO compound nanowire material based on light field irradiation light emitting and photoelectrochemistry performance and preparation method thereof

    CN107604341A

  • Preparation method of solar selective absorbing coating with double-texture surface and coating

    CN114635105A